Current Status for Gastrointestinal Nematode Diagnosis in Small Ruminants: Where Are We and Where Are We Going? - Sarah Jane Margaret Preston; Mark Sandeman; Jorge Gonzalez; David Piedrafita (Journal of Immunology Research)
Gastrointestinal nematode (GIN) parasites pose a significant economic burden particularly in small ruminant production systems. Anthelmintic resistance is a serious concern to the effective control of GIN parasites and has fuelled the focus to design and promote sustainable control of practices of parasite control. Many facets of sustainable GIN parasite control programs rely on the ability to diagnose infection both qualitatively and quantitatively. Diagnostics are required to determine anthelmintic efficacies, for targeted treatment programs and selection of animals for parasite resistant breeding. This review describes much of the research investigated to date to improve the current diagnostic for the above practices which is based on counting the number of parasite eggs in faeces.